The ideal dining room - Trumbull, Laura Helen (My University, 1900)
Introduction: Before treating such a subject as this, it is very necessary for the reader to get the writer’s point of view, as the dining-room which would be ideal for one class of people would not be for another. The dining-room which I am going to discuss is what I would consider ideal for a family of moderate circumstances in the ‘Sunny Land of Kansas’. Our modern dining-room developed from the Elizabethan dining-parlor. No distinction between dining-room and living-room was made until the eighteenth century, and it was not until the middle of the century that they became at all common. Before that time the dining-room was considered unnecessary; but now, among all civilized people, a separate room is set apart in which to dine, as it affords comfort, and it is a well-known fact that food readily absorbs the impurities of the living-room.
Citation: Trumbull, Laura Helen. The ideal dining room. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Dining Room; Home Economics; Theses; Manuscripts (documents)